Highly-skilled migration: between settlement and mobility : IMISCOE short reader (2020)
Simply put, migration is a politicized topic. This applies both to migration itself as well as post-migration integration, and is the case both in the Global North and the Global South. There are, of course, variations in the degree of politicization, but it remains broadly present. However, on the other hand, highly-skilled migrants are one group of migrants who are only rarely politicized or seen in a negative light, both in political and in public discourse (e.g. Heath and Richards 2018). Conventional wisdom has it that highly-skilled migrants are high-earners with needed skills and that they integrate easily and quickly. This perception makes them a “wanted” migration flow (Triadafilopoulos 2013). However, as with most migration flows, there is quite some distance between popular perceptions of this migration flow and the more nuanced picture uncovered by social research. The objective of this Reader is to provide a basic understanding of the migration of the highly-skilled, but also to raise questions and to contribute to closing the divide between popular perception and research-based findings. We should note that the publications we have worked with have been overwhelmingly written in English. We are aware of the wealth of literature in other languages, and hope that others will expand this review beyond the Anglophone works reviewed here. The Reader will thus provide an up-to-date review and critical analysis of literature on highly-skilled migration, within linguistic limits. The review will follow three broad axes of analysis: definition and conceptualization of highly skilled migration; integration of highly-skilled migrants; and emerging patterns of migration and mobility.